Investigating the Fatigue Characteristics of Large Stone Asphalt Mixtures Based on the Disturbed State Concept - Jianhui Wei; Tao Fu; Yongjun Meng; Chengming Xiao (Advances in Materials Science and Engineering)
The mechanical response characteristics of large stone asphalt mixtures (LSAMs) are key factors in studying its fatigue characteristics during cyclic loading tests. Based on disturbed state concept (DSC) and viscoelastic continuum damage model (VECD), a series of tests using an overlay test (OT) were carried out to investigate the fatigue characteristics of LSAM. The results showed that disturbance and damage increased with decreasing frequency and increasing loading displacement and aging degree, while the asphalt content had no obvious adverse effect on the increase in damage. In addition, the disturbance and damage grew rapidly in the early stage of loading and reduced in the later stage of loading. On the contrary, based on DSC, the constitutive model modified with disturbance function (D) defined by external work could describe the mechanical properties, and the evolution process of disturbance function (D) could reflect the damage change in cyclic loading tests. The research conclusion can enrich the theoretical research on the fatigue failure response and mechanism of LSAM under cyclic loading and expand the application scope of DSC in the field of pavement.